Asthma and acute periapical abscesses - Katz Joseph; Rotstein Ilan (Journal of Oral Medicine and Oral Surgery, 2025)
Aim: To assess the prevalence of acute periapical abscesses (PAs) in patients with asthma treated in a large medical facility. Materials and Methods: Integrated data of hospital patients were used. History of asthma diagnosis was retrieved by querying the institutional database in the database. All cases were diagnosed for acute PAs by calibrated dentists in a hospital setting for patients admitted to urgent care. Diagnosis was made based on clinical examination and imaging data confirming the diagnosis of acute PAs without sinus tract. The odds ratio (OR) for the prevalence of acute PAs and its association with history of asthma were calculated. Results: Patients with asthma showed significantly more PAs than patients without asthma (p <0.0001). Females were affected twice as often as males. The odds ratio (OR) for acute PAs in patients with asthma was 3.83, and the difference in prevalence as compared to the total hospital patient population was statistically significant (p <0.0001). No statistical difference was observed in the OR for acute PAs in patients with asthma after adjustment for diabetes mellitus, smoking, and periodontal disease comorbidities. Conclusions: Within the limitations of this study, it appears that the prevalence of acute PAs is significantly higher in patients with a history of asthma.